2020
DOI: 10.1097/qai.0000000000002342
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Sexual Debut Among 14- to 17-year-old Sexual Minority Males: A Preliminary Investigation of Early HIV Risk and Sexual Health Needs

Abstract: Background: Adolescent sexual minority males (ASMM) are disproportionately at risk of HIV. Purpose: This study documents the sexual debut behaviors of ASMM, tests whether sexual debut and sexual behavior differed by race/ethnicity, and explores the association between early anal sex debut and engaging in condomless anal sex. Methods: Sexually active ASMM (N = 118; ages 14–17) in the United States completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Violent experiences, licit/ illicit drug use, homelessness, poverty, and the low level of schooling of youths and their parents increase the chances of poor decision-making and risky behaviours, including those related to sexual behaviour, that are harmful to health [30,31]. Although most of the population of our study have already completed high school and could not receive further intervention in this setting, there is a need to implement sexual health education and school permanence strategies for adolescents to mitigate these effects, especially programmes that consider the specificities of young people in sexual minority groups [32][33][34][35]. Of all the other microorganisms tested, only MH was associated with NG infection.…”
Section: Discussionmentioning
confidence: 98%
“…Violent experiences, licit/ illicit drug use, homelessness, poverty, and the low level of schooling of youths and their parents increase the chances of poor decision-making and risky behaviours, including those related to sexual behaviour, that are harmful to health [30,31]. Although most of the population of our study have already completed high school and could not receive further intervention in this setting, there is a need to implement sexual health education and school permanence strategies for adolescents to mitigate these effects, especially programmes that consider the specificities of young people in sexual minority groups [32][33][34][35]. Of all the other microorganisms tested, only MH was associated with NG infection.…”
Section: Discussionmentioning
confidence: 98%
“…Intercourse may be considered a weaker indicator of sexual development among sexual minority youth [ 49 ]. However, research has shown that adolescents identifying with sexual minorities may have experiences of intercourse even more commonly and earlier than heterosexually identifying peers [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between youth experiences of forced sexual intercourse and adverse mental health outcomes have been well established [55,56]. However, only a few examined the association between ESI and negative mental health outcomes [27,35,36,[57][58][59], and the results are mixed [37,60]. Therefore, the objective of this study was to examine the association between ESI, forced sexual intercourse and SV victimization, symptoms of depression, and suicidal behaviors among adolescents who had ever had sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…A burgeoning number of studies investigating ESI have found that ESI is associated with various sexual risk behaviors such as sex without regular condom use, having multiple sexual partners, sex under the influence of alcohol or drugs, and transactional sex [22][23][24][25]. ESI has also been found to be associated with unintended pregnancy [21,26], sexually transmitted infections (STIs) [16,19,27], and increased risk of contracting human immunodeficiency virus (HIV) [28,29]. Samek et al [30] examined data on 1512 adolescent same-sex twins from the Minnesota Twin Family Study and found that ESI was significantly associated with subsequent sexual-risk taking behaviors.…”
Section: Introductionmentioning
confidence: 99%